NON-TRADITIONAL DRAWING TECHNIQUES FOR THE DEVELOPMENT OF IMAGINATION FOR STUDENTS WITH MILD MENTAL DISABILITIES - Rozenfelde, Marite; Bogurdovicha, Svetlana; Teresko, Aija (Education Reform: Education Content Research and Implementation Problems, 2021)
Imagination development for pupils with mild mental disorders requires special attention and special pedagogical approach, because independent and creative thinking skills, initiative of creative activity cannot develop by itself; it is not a side effect of knowledge acquisition, it needs to be promoted and activated. The paper raises the issue of the importance of imagination development and opportunities for pupils with mild mental disorders during extracurricular activities, using non-traditional drawing techniques. The paper provides information about the collection of non-traditional drawing techniques developed and approbated by S. Bogurdovicha.